The magnitude and risk factors of intestinal parasitic infection in relation to human immunodeficiency virus infection and immune status, at ALERT hospital, Addis Ababa, Ethiopia - Taye, Biruhalem (2015)
Human Immunodeficiency Virus (HIV) and intestinal parasitic infections are among the main health problems in developing countries like Ethiopia. Particularly, co-infections of these diseases would worsen the progression of HIV to Acquired Immunodeficiency Syndrome (AIDS). The purpose of this study was to determine the magnitude and risk factors for intestinal parasites in relation to HIV infection and immune status. The study was conducted in (1) HIV positive on antiretroviral therapy (ART) and (2) ART naïve HIV positive patients, and (3) HIV-negative individuals, at All African Leprosy and Tuberculosis (TB) Eradication and Rehabilitation Training Center (ALERT) hospital in Addis Ababa, Ethiopia. Study participants were interviewed using structured questionnaires to obtain socio-demographic characteristics and assess risk factors associated with intestinal parasitic infection. Intestinal parasites were identified from fecal samples by direct wet mount, formol ether concentration, and modified Ziehl-Neelsen staining techniques. The immune status was assessed by measuring whole blood CD4 T-cell count. The overall magnitude of intestinal parasite was 35.08%. This proportion was different among study groups with 39.2% (69/176), 38.83% (40/103) and 27.14% (38/140) in ART naïve HIV positives patients, in HIV negatives, and in HIV positive on ART patients respectively. HIV positive patients on ART had significantly lower magnitude of intestinal parasitic infection compared to HIV negative individuals. Intestinal helminths were significantly lower in HIV positive on ART and ART naïve patients than HIV negatives. Low monthly income, and being married, divorced or widowed were among the socio-demographic characteristics associated with intestinal parasitic infection. No association was observed between the magnitude of intestinal parasites and CD4 T-cell count. However, Cryptosporidium parvum, and Isospora belli were exclusively identified in individuals with CD4 T-cell count of ≤ 350 cells/mm(3). Regular provision of mass preventive chemotherapy and extended health education will curb the burden of intestinal parasitic infection in the community. Emphasis should also be given to laboratory diagnosis and identification of opportunistic intestinal parasites in patients with lower CD4-Tcell count.